Celostni pristop k medvrstniškemu nasilju: Psihosocialni konteksti in raziskovalne strategije - Špes, Tanja; Horvat, Marina; Zorjan, Saša; Peras, Igor; Markovič, Rene; Pečjak, Sonja; Pirc, Tina; Kozina, Ana; Koračin, Tinkara; Kranjec, Eva; Tina Pivec, Tina Pivec; Ana Lampret, Ana Lampret; et al. (University of Maribor Press, 2025)
An Integrated Approach to Bullying: Psychosocial Contexts and Research Strategies. Bullying is a complex phenomenon, embedded in a social context, and needs to be studied using different approaches and involving different perspectives. This scientific monograph presents the key findings of a project in which we used multiple data sources (self-report, peer nominations, teacher reports) and advanced research designs (longitudinal study, focus groups) to explore the reciprocal relationship between the psychosocial characteristics of students and classrooms and students’ involvement in bullying in early adolescence. In addition, we examined the role of individual and class psychosocial characteristics and involvement in bullying in relation to students’ school adjustment. The project consisted of two studies: a three-measure longitudinal core study with a large sample of adolescents, and a qualitative study. Based on the findings of both surveys, we developed guidelines for the design of prevention and intervention activities to support such classroom contexts, which are a protective factor for bullying prevention in adolescence.